Aplicação de Aeronave Remotamente Pilotada (Drone) em Engenharia Civil - levantamento bibliográfico e estudo de caso - Bernardo, Maria Emanuela Conceição (Brasil, 2021)
The Remotely Piloted Aircraft – RPA (Remotely Piloted Aircraft), has been increasingly applied in the areas of Civil Engineering. Despite being a very relevant technological resource, as it is a relatively recent innovation, it is still not much bibliographically referenced to support its use. It is important to disseminate this technology, which is constantly on the rise and will be another important ally to obtain data with accurate and quality results, in addition to optimizing processes in Engineering. In this work, firstly, a Theoretical Framework is presented, the professional is aware of the functionality and characteristics of this equipment, its mode of operation, the normative guidelines and the different models that have different applications, classifications and characteristics. The first case with applications of the tool to spread this artifice and highlight its various functions is also presented, in order to register and communicate its use in Civil Engineering/Civil Construction. In the second case, the topographic survey by RPA is displayed to show its results through the case study in parallel with a conventional resource. Therefore, this work starts from the hypothesis that this resource will soon be essential and indispensable since there is potential for growth in the market and in the scientific environment, as a great tool for obtaining information.